2014
DOI: 10.4028/www.scientific.net/ast.93.174
|View full text |Cite
|
Sign up to set email alerts
|

Development of Plasmonic Photocatalysts for Environmental Application

Abstract: Regarding catalytic and plasmonic properties of gold nanoparticles (NPs), the novel area of research on photocatalytic gold properties has been recently started. In contrast with catalytically active gold NPs, where nanosized gold is recommended, our results showed that polydispersity of deposited gold NPs on semiconducting support was beneficial for photocatalytic activity under visible light irradiation. It is thought that wide size/shape distribution of gold NPs, and thus the ability of absorption of light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…1 a. It is thought that low activity of silver-modified titania for hydrogen evolution (much lower than that of gold- and/or platinum-modified titania [45] , [53] , [54] , due to (i) similar work function of silver and electron affinity of titania, and (ii) high activation overpotential for hydrogen evolution on silver) caused negligible differences in activity between all samples. It was found that formation of Ag NPs was completed during first 2 h of irradiation since after this time linear evolution of hydrogen was noticed (as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 a. It is thought that low activity of silver-modified titania for hydrogen evolution (much lower than that of gold- and/or platinum-modified titania [45] , [53] , [54] , due to (i) similar work function of silver and electron affinity of titania, and (ii) high activation overpotential for hydrogen evolution on silver) caused negligible differences in activity between all samples. It was found that formation of Ag NPs was completed during first 2 h of irradiation since after this time linear evolution of hydrogen was noticed (as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Silver (Ag) as a relative cheap noble metal has great potential for the application of plasmonic photocatalysis not only due to its plasmon resonance but also the excellent anti-microbiological (anti-fungal and anti-bacterial) properties. [44] , [45] , [46] In previous study on OAPs it was found that the preparation conditions had important influence on the physicochemical properties of titania (specific surface area, crystallite size, crystallinity, surface composition) including the morphology (the content of faceted NPs), and thus on the photocatalytic activity [47] , [48] . To investigate how the properties of titania influence the modification with Ag, as well as how the resultant properties of Ag-modified OAPs influence the photocatalytic activity, OAPs samples varied by properties were prepared by ultrasonication-hydrothermal (US-HT) method and then modified with Ag NPs by photodeposition.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most interesting finding indicates that small differences in sizes of deposited metal NPs resulted in large difference in kind and level of antibacterial properties, i.e., silver deposition on the FP6 titania from water resulted in formation of larger NPs of larger antibacterial activity under visible light irradiation than silver deposited from methanol which showed much higher activity under dark conditions [34,35].…”
Section: Antibacterial Propertiesmentioning
confidence: 96%
“…However, in the present study UV lamps have been avoided due to necessity of development of environmental friendly materials able to work under natural solar radiation. Our recent research on Penicillum chrysogenum has proved that modification of titania with nanoparticles of noble metals being able to absorb visible light (due to plasmon resonance) caused inhibition of both fungal growth and production of mycotoxins under irradiation with visible light (25).…”
Section: Resultsmentioning
confidence: 99%